Uma metodologia analítica rápida para quantificação simultânea de estrógenos em águas usando HPLC-DAD e calibração de segunda ordem - Segundo Neto, José Licarion Pinto (2014)
With the increasing use of manufactured products such as pharmaceuticals, cosmetics and toiletries, a new category of water bodies pollutants, called emerging contaminants, is gaining prominence in the environmental issues and preservation scenario of the planet's fresh water. Among these are endocrine disruptors, such as estrogens that has concerned the scientific community that has been warning for need to establish maximum concentration levels of these types of substances in the drinking water. Parallel to the legislation s rises to control these pollutants is necessary the development of rapid analytical methodologies, robust and with low waste generation. Almost all the analytical methods for quantification of estrogens in water samples make use of liquid or gas chromatography coupled to mass spectra associated to long chromatographic runs. In this work a fast method is presented for simultaneous quantification of four estrogens (E1, E2, E3 and EE2) in surface water samples using HPLC-DAD and multiway calibration with the purpose to exploit the potentialities of the second order advantage to circumvent the problems of sample complexities. Second order calibration models based on PARAFAC, MCR-ALS, N and U-PLS/RBL methods were constructed using individual pattern of analytes (pure standard) solutions. These models were then validated using a set of synthetic mixtures of these analytes with two potential interferences (daizein and biochanin A) to simulate the organic load and to demonstrate second order advantage. Satisfying statistical validation parameters were obtained, especially for U and N-PLS/RBL models. Finally river and sewage samples fortified with four estrogens were subjected to a pre-concentration and sample clean up using SPE-C18 cartridge followed by chromatographic analysis. The application of the calibration model to the fortified waters' samples led to, most cases, a recovery between 70 and 120%, reflecting the good accuracy of the proposed method